Synthesis, characterization and constitutional isomerism study of new aromatic polyamides containing pendant groups based on asymmetrically substituted meta-phenylene diamines - Pal, Ravindra R.; Patil, Prashant S.; Salunkhe, Manikrao M.; Maldar, Noormahamad N.; Wadgaonkar, Prakash P. (European Polymer Journal, 2009)
Four new aromatic polyamides containing pendant groups were synthesized by low temperature interfacial polycondensation of two asymmetrically substituted diamine monomers, namely, 4-[4-(1-methyl-1-phenylethyl) phenoxyl-1,3-diamino benzene and 4-[4-[4-methylphenyl) sulphonyl]phenoxy)-1,3-diamino benzene with two aromatic diacid chlorides, namely isophthaloyl chloride and tereplithaloyl chloride. Inherent viscosities of polyamides were in the range 0.64-0.72 dL/g indicating formation of medium molecular weight polymers. The weight average molecular weights and number average molecular weights, determined by gel permeation chromatography (polystyrene standard), were in the range 54,500-65,000 and 19,750-27,000, respectively. The constitutional isomerism of synthesized polyamides was investigated by (1)H and (13)C NMR spectroscopy, where as the constitutional order was calculated from (1)H NMR spectroscopy and was found to be in the range 0.35-0.37. Polyamides containing pendant groups were essentially amorphous and were soluble in polar aprotic solvents such as N, N-dimethyl acetamide, N-methyl-2-pyrrolidone, N, N-dimethyl formamide and dimethyl sulfoxide. Polyamides exhibited glass-transition temperature in the range 237-254 degrees C. The initial decomposition temperature, determined by TGA in nitrogen atmosphere, of polyamides was in the range 371-410 degrees C indicating their good thermal stability. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Asymmetrically substituted diamines; Constitutional isomerism; interfacial polycondensation; Pendant groups